Pemanfaatan Aplikasi Flexnote Suite Accounting Untuk Pengelolaan Pencatatan Akuntansi Dan Operasional Perusahaan - Citra Nailus Sa’ida Rahma; Asna Rafiska Hardini; Lies Nurhaini (BADAN PENERBIT STIEPARI PRESS, 2023)
Commonly used record-keeping applications by many companies include Accurate, MYOB, Zoho, Zahir, SAP, Scylla, Sage, and Oracle, each with its own advantages and disadvantages that need to be considered before being used by a company. Therefore, the purpose of this research is to analyze the use of the Flexnote application as one of the ERPs used in the company. The research approach used is qualitative descriptive with data collection methods such as direct observation, interviews, and literature studies. Based on the analysis results, it can be concluded that the Flexnote Suite Accounting application is one type of ERP created by a developer company from Surabaya that functions to facilitate the operational processes of the company, including sales, stock, finance, and accounting. Flexnote is still not perfect as an ERP in a company, with its strengths and weaknesses.